Chronic total occlusion percutaneous coronary interventions: identifying patients at risk of complications. (3rd May 2020) - Neupane, Saroj; Gupta, Ankur; Basir, Mir; Alaswad, Khaldoon
ABSTRACT: Introduction: Angina refractory to medical therapy and providing complete revascularization (after acute coronary syndrome or in patients with ischemic cardiomyopathy) are common indications for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Unfortunately, CTO PCI is associated with higher rates of complications when compared with non-CTO PCI. Areas covered: In this article, we review available studies on risk prediction in CTO PCI and outline strategies to avoid complications. Expert opinion: Identifying patients at increased risk of periprocedural major adverse cardiovascular events (MACE) is of great importance. It enhances the conversations about the risk and benefits of CTO PCI and it allows for shared decision making when deciding to undergo or forego such procedures.